Efecto del almidón de yuca a partir de diferentes porcentajes de camarón y pollo en la textura final de una salchicha - Loor Artega, Luis Manuel (2017)
The purpose of this research is to determine the effect of cassava starch caused by different percentages of shrimp and chicken in the final texture of a sausage by applying the factors: percentages of cassava starch (a) A1 = 5% and A2 = 6%, percentage of shrimp and chicken (b) b1 = Chicken 40%: Shrimp 20%, b2 = Chicken 30%: Shrimp 30% , B3 = 20% chicken: 40.se Shrimp applying DCA (completely random design) with a * b bifactorial arrangement using three replies per treatment, (ANOVA) variance test was used for data analysis, Kruskal-Wallis test and Tukey's test 5% significance. We assessed the variables chewability, elasticity, firmness and hardness by testing TPA (Analysis texture profile). The results obtained in the assumptions of the ANOVA the hardness and firmness were significant therefore test of Levene was applied in which it turned out that it was not significant, in relation to elasticity and mastication were not significant so it was applied tests of Kruskal-Wallis, this test applied to the variables above mentioned in the factors as the treatments were not significant. Regarding the acceptability of the sausage the judges considered good due to the T1 presented better sensory characteristics. The characterization bromatological was obtained: fat 6.5% and protein 23.27% and microbiologically was not detected Salmonella sp. 22, Staphylococcus aureus < 1 cfu/G, Escherichia coli < 1.5 x 10 CFU/URg.se concluding that by analyzing the texture profile It was found that both, the factors and treatments were not significant, indicating that they had no influence on the final texture of the shrimp and chicken sausage.